MARTIN, J.R. e ROSE, D. Genre relations ”“ maping culture . Equinox: London/Oakvile, 289 páginas, 2008. - Bonfim, João Bosco Bezerra (Cadernos de Linguagem e Sociedade, 2011)
MARTIN, J.R. e ROSE, D. Genre relations ”“ maping culture . Equinox: London/Oakvile, 289 páginas, 2008.